A Discriminant Model to Assess the Entrepreneurial Talent of MBA Students in Bangalore : An Empirical Study - Chavadi, Chandan A.; Sirothiya, Monika (Prabandhan: Indian Journal of Management, 2018)
Entrepreneurs are the harbingers of new innovation and fresh ideas; they play a starring role in the economic improvement of a nation by providing employment opportunities and creating wealth. It is believed that business management courses foster entrepreneurship & innovations, and the ability of the entrepreneurs decides the success or failure of an enterprise. This paper attempted to find out why some entrepreneurs succeed and some don't, and what are the predictors of entrepreneurial success. The findings of the study revealed that entrepreneurial traits and business skills were better predictors of successful and unsuccessful entrepreneurs than entrepreneurial attitude. Further, to fathom the distinctive personalities of entrepreneurs, cluster analysis was performed. The four segments identified were lifestyle entrepreneurs, profit-seeker entrepreneurs, drone entrepreneurs, and innovative entrepreneurs. For this study, 103 entrepreneurs, who were MBA graduates, were approached. This research study developed a discriminant model which can classify new cases into successful or unsuccessful entrepreneurs. This study would be useful to bank managers, financial service providers, angel investors, & both aspiring and existing entrepreneurs.